1985
DOI: 10.1002/ajpa.1330280507
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in environmental sensitivity during growth and development

Abstract: Data on sex differences in mortality, morbidity, growth under conditions of environmental stress, and growth responses to environmental improvement are reviewed to test the hypothesis that males are less buffered than females against the environment during growth and development. The hypothesis predicts that males should be more affected by environmental stress, and the strongest support for this is found in studies of the prenatal period. Under stressful conditions, males have higher late fetal mortality than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
286
3
16

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 399 publications
(331 citation statements)
references
References 110 publications
(106 reference statements)
26
286
3
16
Order By: Relevance
“…These findings also corroborate those reported for adolescents in Jamaica (Jackson et al, 2002), Brazil (Wang et al, 2002), China (Hesketh et al, 2002;Wang et al, 2002) and Bolivia (Pérez-Cueto et al, 2005). Thus, our study may have certain implications with respect to the observation that boys are more vulnerable than girls to adverse conditions, such as infections and/or nutritional deprivation (Tanner, 1962;Stinson, 1985;Worthman, 1996), notwithstanding other risks of different obstetric complications (Mizuno, 2000). It is well known that boys are, on average, larger than girls until the beginning of the adolescent growth spurt in girls.…”
Section: Role Of Biological Factorssupporting
confidence: 90%
See 1 more Smart Citation
“…These findings also corroborate those reported for adolescents in Jamaica (Jackson et al, 2002), Brazil (Wang et al, 2002), China (Hesketh et al, 2002;Wang et al, 2002) and Bolivia (Pérez-Cueto et al, 2005). Thus, our study may have certain implications with respect to the observation that boys are more vulnerable than girls to adverse conditions, such as infections and/or nutritional deprivation (Tanner, 1962;Stinson, 1985;Worthman, 1996), notwithstanding other risks of different obstetric complications (Mizuno, 2000). It is well known that boys are, on average, larger than girls until the beginning of the adolescent growth spurt in girls.…”
Section: Role Of Biological Factorssupporting
confidence: 90%
“…It has been suggested that vulnerability to poor environmental conditions, such as infections and nutritional deprivation is greater in boys than in girls (Tanner, 1962;Waldron, 1983;Stinson, 1985;Worthman, 1996). Nutrition surveys at the national level in many developing countries have revealed that nutritional status, as indicated by anthropometric indicators, is better among girls than among boys aged below 5 y (Marcoux, 2002;Garenne, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The result that only male health and aging is significantly affected by the season of birth is consistent with the finding of larger season-of-birth effects for men on life expectancy (Doblhammer and Vaupel, 2001;Lerchl, 2004) and on adult body size (Krenz-Niedbala, 2011) and with the general notion that males are more responsive to adverse environmental conditions in early life (Stinson, 1985). As a potential explanation it has been proposed that boys grow faster than girls in the womb such that the size of the placenta relative to body size of the newborn is smaller for boys and thus provides less buffer capacity to nutritional shocks experienced by the mother (Erikson et al, 2010).…”
Section: Introductionsupporting
confidence: 85%
“…A heightened sensitivity of male fetuses to maternal nutrition is suggested in humans by the finding in some studies that nutritional supplementation of poorly nourished mothers disproportionately improves male birth weight (Mora et al, 1979;Adair & Pollitt, 1985), and that male embryos or fetuses suffer higher pregnancy losses under conditions of maternal undernutrition (Andersson & Bergstrom, 1998). If the greater male sensitivity to prenatal nutrition or stress (Stinson, 1985) manifests as sex differences in postnatal lipid profiles or CVD risk, sex differences might be accentuated in this population owing to the marginal nutritional status of the mothers during pregnancy.…”
Section: Sex Differences In Lipid Programming: Hypothesesmentioning
confidence: 99%